Fecal lactoferrin accurately reflects mucosal inflammation in inflammatory bowel disease - Rubio, Marrieth G (World J Gastrointest Pathophysiol, 2019)
BACKGROUND: Studies have demonstrated a potential role for fecal biomarkers such as fecal calprotectin (FC) and fecal lactoferrin (FL) in monitoring inflammatory bowel diseases (IBD) - Crohn’s disease (CD) and ulcerative colitis (UC). However, their correlation to endoscopic scores, disease severity and affected intestinal surface has not been extensively investigated. AIM: To correlate FL, and for comparison white blood cell (WBC) and C-reactive protein (CRP), with endoscopic scores, disease extent and location in CD and UC. METHODS: Retrospective analysis in 188 patients who had FL, CRP and WBC determined within 30 d of endoscopy. Disease location, disease extent (number of intestinal segments involved), disease severity (determined by endoscopic scores), timing of FL testing in relation to colonoscopy, as well as the use of effective fast acting medications (steroids and biologics) between colonoscopy and FL measurement, were recorded. RESULTS: In 131 CD and 57 UC patients, both CRP and FL - but not WBC - distinguished disease severity (inactive, mild, moderate, severe). In patients receiving fast-acting (steroids or biologics) treatment in between FL and colonoscopy, FL showed a higher correlation to endoscopic scores when tested before vs after the procedure (r = 0.596, P < 0.001, vs r = 0.285, P = 0.15 for the Simple Endoscopic Score for CD; and r = 0.402, P = 0.01 vs r = 0.054 P = 0.84 for Disease Activity Index). Finally, FL was significantly correlated with the diseased mucosal surface (colon-ileocolon > small bowel) and the number of inflamed colon segments. CONCLUSION: FL and CRP separated disease severity categories with FL showing lower discriminating P-values. FL showed a close correlation with the involved mucosal surface and with disease extent and was more closely correlated to endoscopy when determined before the procedure – this indicating that inflammatory activity changes associated with therapy might be rapidly reflected by FL levels. FL can accurately and timely characterize intestinal inflammation in IBD.